2020
DOI: 10.3389/fpls.2020.00724
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor GmWRKY142 Confers Cadmium Resistance by Up-Regulating the Cadmium Tolerance 1-Like Genes

Abstract: Cadmium (Cd) is a widespread pollutant that is toxic to living organisms. Previous studies have identified certain WRKY transcription factors, which confer Cd tolerance in different plant species. In the present study, we have identified 29 Cd-responsive WRKY genes in Soybean [Glycine max (L.) Merr.], and confirmed that 26 of those GmWRKY genes were up-regulated, while 3 were down-regulated. We have also cloned the novel, positively regulated GmWRKY142 gene from soybean and investigated its regulatory mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 80 publications
1
36
0
Order By: Relevance
“…These outcomes prove that ABA negatively modulates the expression of WRKY12 and WRKY142 in soybean plants. Previous studies showed that the enhanced expression of GmWRKY12 and GmWRKY142 led to improved salt and cadmium tolerance, augmented proline content and alleviated malondialdehyde content under salt and cadmium treatment in soybean seedlings [33,34]. In sum, our findings tied to GmWRKY12, GmWRKY142, ABA, and SA quantities in AMP treated seedlings enable us to assume that AMP assists stressed plants to deal with numerous abiotic stresses.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These outcomes prove that ABA negatively modulates the expression of WRKY12 and WRKY142 in soybean plants. Previous studies showed that the enhanced expression of GmWRKY12 and GmWRKY142 led to improved salt and cadmium tolerance, augmented proline content and alleviated malondialdehyde content under salt and cadmium treatment in soybean seedlings [33,34]. In sum, our findings tied to GmWRKY12, GmWRKY142, ABA, and SA quantities in AMP treated seedlings enable us to assume that AMP assists stressed plants to deal with numerous abiotic stresses.…”
Section: Discussionsupporting
confidence: 66%
“…Then, we aimed to decipher how exogenous ampelopsin application influences the physiochemical attributes of salinity and heavy metal damaged plants by examining growth alterations, fatty acid contents, amino acid contents and antioxidant contents. Moreover, we evaluated the transcription patterns of various genes, including GmWRKY12 and GmWRKY142 [33,34], GmNAC109 [35], GmERF75 [36], GmFDL19 [37], GmSAP16 [38], GmFAD3 [37], and GmAPX [39], to confirm our physiochemical findings.…”
Section: Introductionmentioning
confidence: 60%
“…Overexpression of WRKY12 and WRKY13 reduces Cd accumulation and enhances Cd tolerance. The overexpression of GmWRKY142 in Arabidopsis and soybean hairy roots reduced Cd uptake and significantly enhanced tolerance ( Zhang C. Z. et al, 2020 ). However, overexpression of CaWRKY41 in Arabidopsis could enhance the absorption of Cd and Zn and reduce tolerance ( Dang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…[112]. GmWRKY142 directly regulates the stress-related genes to reduce the Cd absorption and actively regulate Cd tolerance in plants (e.g., Glycine max) [113]. The transcription factor WRKY13 positively regulates Cd tolerance in arabidopsis by activating the PDR8 (ABC transporter), a Cd effector pump that reduces Cd accumulation by pumping Cd 2+ from the cytoplasm to the ectoplasm [114].…”
Section: Plant Tfs and Mirnas Play Important Roles In Regulating Metal Homeostasismentioning
confidence: 99%